2007
DOI: 10.1007/s11096-005-2905-4
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study on the effect of pharmacist counseling on awareness of and willingness to quit smoking in Malaysian population

Abstract: Increase in awareness of and willingness to quit smoking reflects that pharmacist counseling seems to be helpful in cessation of smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…The scoping exercise identified nine papers on smoking cessation [13,42–49] . In a cross‐sectional study, it was reported that increased awareness and the willingness to quit smoking is a sign that pharmacist counselling seems to be helpful in smoking cessation [47] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The scoping exercise identified nine papers on smoking cessation [13,42–49] . In a cross‐sectional study, it was reported that increased awareness and the willingness to quit smoking is a sign that pharmacist counselling seems to be helpful in smoking cessation [47] .…”
Section: Resultsmentioning
confidence: 99%
“…[13,[42][43][44][45][46][47][48][49] In a cross-sectional study, it was reported that increased awareness and the willingness to quit smoking is a sign that pharmacist counselling seems to be helpful in smoking cessation. [47] This evidence is also supported by another study revealing that the initiatives to increase pharmacists' tobacco-related knowledge, as well as the skills to enhance their sense of responsibility in health promotion, may promote the ability of pharmacists to provide consultancy services with accuracy and effectiveness. [48] In a randomised controlled trial, the authors concluded that increased engagement of pharmacists in tobacco cessation is likely to have a significant impact on smoking rates, prevention of tobaccorelated diseases and overall improvement in public health.…”
Section: Provision Of Smoking Cessation Servicesmentioning
confidence: 99%
“…8 Babar et al reported that opportunities exist for Malaysian pharmacists to render services in smoking cessation. 9 Despite these opportunities, Malaysian pharmacists were not contributing optimally in this area. 10,11 Lack of comprehensive tobacco-related courses and training in most universities' curricula was cited as a major contributing factor, as well as lack of in-service training and continuing professional development (CPD) programs focusing on the subject.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacists and pharmacies in many countries have important roles in promoting public health 1–8 . Today's US pharmacists and pharmacies have ample opportunities to expand traditional pharmacist responsibilities of dispensing pharmaceuticals to engage in preventing diseases, prolonging healthy life and promoting health 9 .…”
Section: Introductionmentioning
confidence: 99%